Clinical, epidemiological and laboratory features of Salmonellosis in children at the present stage - E. G. Klimovitskaya; S. N. Eshmolov; I. G. Sitnikov (Детские инфекции (Москва))
In recent years, there has been an increase in the incidence of salmonellosis in children, including in the Yaroslavl region by 52.7%.In order to study salmonellosis in children at the present stage, we observed 185 patients aged from 1 month to 18 years who were hospitalized in the Infectious Clinical Hospital of the city of Yaroslavl from 2015 to 2017. The analysis of the main clinical, epidemiological and laboratory parameters was carried out and the peculiarities of the course of salmonellosis in children were established.Results: Salmonella enteritidis remains the dominant pathogen. The children of the first 3 years of life prevailed — 65.4%, of which under the age of 1 year — 18.9%, unorganized in preschool institutions — 49.2%. Alimentary infection was found in 49.7% of cases. In 71.4% of patients, the disease developed against a background of concomitant pathology. In most cases (74.1%), damage to the gastrointestinal tract was manifested by gastroenterocolitis or enterocolitis. In 38.9% of cases, salmonellosis occurred in combination with bacterial and viral pathogens, especially with rota and noroviruses (81.9%), which aggravated the course of the infection. Severe forms accounted for 24.9% and were due to the development of dehydration, mainly in patients with mixed infections.